Using cognitive strategies in mobile-assisted language learning to enhance listening ability among EFL learners - Guofang Xiong; Wendy Hiew (Global Academic Excellence, 2024)
The advent of Mobile-Assisted Language Learning (MALL) has revolutionized the field of English as a Foreign Language (EFL) education by providing learners with unprecedented access to language learning resources anytime and anywhere. Among the various skills in language acquisition, listening is often considered one of the most challenging to master. Therefore, it is important to implement effective strategies to enhance listening comprehension. This study examined the role of cognitive strategies in enhancing EFL listening abilities among learners by using MALL, with the aim to investigate what cognitive strategies students used during their listening practice with the MALL method. The qualitative research method was adopted and the students’ listening journals were collected and analyzed by using the thematic analysis to conduct the research. Results of the study indicated that meta-cognitive, cognitive, and social-affective strategies were used in students’ listening practice. Some other useful points were also found to guide the future MALL research in EFL listening practice. The findings are expected to provide insights for effectively incorporating cognitive strategies with MALL method in EFL listening studies so as to improve listening efficiency and inform instructional practices in the EFL classroom.